(untitled) (American Journal of Islam and Society, 2009)
Although the young and beautiful Europa was kidnapped by Zeus, the most important hero of Greek mythology, she has given a general identity to that continent which bears her name. Debates about the exact location of “Europe” and the definition of “Europeanness” have been going on for centuries. 1 Europe has borne its complex identity as a continent until recent times; however, due to its surrounding regions and especially its culturopolitical definitions, it does not have either geographically or culturally exact boundaries. In fact, the positive meaning given in general to “Europe” and “Europeanness” in modern times has increased the number of countries or population groups that wish to share this identity. But “otherness,” the unavoidable face of identity, has created an even more complex situation that is now intertwined with this positive meaning. As distinct from “Westernism,” the concept of “Europeanness” has developed not only in terms of identity but also in terms of values, especially after the Second World War.2 The performance shown in such issues as the continuity of welfare and peace, stability, and democracy, as well as the respect for human rights, cultural richness, and individual development, has had a great impact upon it.Although in the recent past Europe was a continent of horrible atrocity, intolerance, and war, it can be said that within the space of fifty years, it has largely effaced this negativity and is actively trying to be accepted as the symbol of “what is right and good.” ...